Virtual medical astronaut avatars for future deep space missions - Urlings, Carole; Baselet, Bjorn; Tabury, Kevin; Baatout, Sarah (Frontiers in Space Technologies, 2024)
This paper explores the telemedicine possibilities available to astronauts during spaceflight, focusing on the possible utilization of medical avatars for continuous health monitoring. Various types and sources of telemedicine are examined, along with their applications in deep space travel to address the challenges faced by astronauts and facilitate timely intervention in case of injuries and illnesses. The use of medical avatars presents a promising solution to mitigate risks and ensure effective healthcare delivery in the absence of immediate physical medical support. Furthermore, potential terrestrial applications of telemedicine and virtual medical avatars are discussed, highlighting the wider implications and benefits beyond space exploration. By leveraging advanced technologies and innovative approaches, telemedicine in conjunction with medical avatars offers a compelling avenue for enhancing healthcare practices both in space and on Earth.